Association of Apolipoprotein E ɛ4 Allele with Enlarged Perivascular Spaces. Issue 1 (27th April 2022) - Pinheiro, Adlin; Demissie, Serkalem; Scruton, Ashlea; Charidimou, Andreas; Parva, Pedram; DeCarli, Charles; Seshadri, Sudha; Romero, José R.
Abstract : Objective: Enlarged perivascular spaces have emerged as markers of cerebral small vessel disease and are linked to perivascular drainage dysfunction. The apolipoprotein E‐ɛ4 (APOE‐ɛ4) allele is the strongest genetic risk factor for cerebral amyloid angiopathy and Alzheimer's neuropathology, but the underlying mechanisms remain unclear. We studied the relationship between APOE‐ɛ4 and the topography and burden of enlarged perivascular spaces to elucidate underlying mechanisms between APOE‐ɛ4 and adverse clinical outcomes. Methods: We included 3, 564 Framingham Heart Study participants with available genotypes and magnetic resonance imaging. Enlarged perivascular spaces in the basal ganglia and centrum semiovale were rated using a validated scale. We related APOE‐ɛ4 allele presence to high burden of enlarged perivascular spaces in each region and a mixed score reflecting high burden in both regions using multivariable logistic regression. Exploratory analyses incorporated presence of cerebral microbleeds and assessed effect modification by hypertension. Results: Mean age was 60.7 years (SD = 14.6), 1, 644 (46.1%) were men, 1, 486 (41.8%) were hypertensive, and 836 (23.5%) participants were APOE‐ɛ4 carriers. APOE‐ɛ4 was associated with high burden of enlarged perivascular spaces in the centrum semiovale (odds ratio [OR] = 1.45, 95% confidence interval [CI] = 1.16, 1.81) and mixed regions (OR = 1.37, 95% CI = 1.11, 1.68). Associations were slightly stronger in hypertensive subjects. Interpretation: The APOE‐ɛ4 allele plays a modest role in the burden of enlarged perivascular spaces in the centrum semiovale. Further studies are needed to clarify the underlying small vessel disease type in community‐dwelling individuals with predominant centrum semiovale enlarged perivascular spaces, which may be hypertensive angiopathy in our sample. ANN NEUROL 2022;92:23–31